2021
DOI: 10.3389/fimmu.2021.624310
|View full text |Cite
|
Sign up to set email alerts
|

IBT-V02: A Multicomponent Toxoid Vaccine Protects Against Primary and Secondary Skin Infections Caused by Staphylococcus aureus

Abstract: Staphylococcus aureus causes a wide range of diseases from skin infections to life threatening invasive diseases such as bacteremia, endocarditis, pneumonia, surgical site infections, and osteomyelitis. Skin infections such as furuncles, carbuncles, folliculitis, erysipelas, and cellulitis constitute a large majority of infections caused by S. aureus (SA). These infections cause significant morbidity, healthcare costs, and represent a breeding ground for antimicrobial resistance. Furthermore, skin infection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 83 publications
(118 reference statements)
4
32
0
Order By: Relevance
“…Integrated Bio Therapeutics has developed a heptavalent S. aureus vaccine consisting of seven S. aureus toxoids: Hla, Panton–Valentine Leukocidin (PVL) F and S subunits, Leukocidin A/B, SEA, SEB, and Toxic shock syndrome toxin 1. Preclinical data have shown that this vaccine, named IBT-V02, confers protection to both mice and rabbits against S. aureus skin infection, with protection being entirely mediated by vaccine-induced antibodies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrated Bio Therapeutics has developed a heptavalent S. aureus vaccine consisting of seven S. aureus toxoids: Hla, Panton–Valentine Leukocidin (PVL) F and S subunits, Leukocidin A/B, SEA, SEB, and Toxic shock syndrome toxin 1. Preclinical data have shown that this vaccine, named IBT-V02, confers protection to both mice and rabbits against S. aureus skin infection, with protection being entirely mediated by vaccine-induced antibodies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…IBT-VO2 is a multivalent vaccine currently under investigation. α-hemolysin, PVL LukS, LukF, LukAB, enterotoxins A and B, and toxic shock syndrome toxin 1 toxoids are all included in this heptavalent vaccine [167]. The multi-subunit vaccine generates an antibody response that is cross-reactive with 12 to 15 S. aureus toxins and gives protection in different mice and rabbit infection models due to structural similarities [167].…”
Section: Vaccinesmentioning
confidence: 99%
“…α-hemolysin, PVL LukS, LukF, LukAB, enterotoxins A and B, and toxic shock syndrome toxin 1 toxoids are all included in this heptavalent vaccine [167]. The multi-subunit vaccine generates an antibody response that is cross-reactive with 12 to 15 S. aureus toxins and gives protection in different mice and rabbit infection models due to structural similarities [167]. Recently, IBT-VO2 entered a Phase I clinical study after completing the encouraging pre-clinical phase, and as a result, received additional funding to help it progress.…”
Section: Vaccinesmentioning
confidence: 99%
“…Integrated BioTherapeutics have developed a heptavalent S. aureus vaccine consisting of seven S. aureus toxoids: Hla, Panton-Valentine Leukocidin (PVL) F and S subunits, Leukocidin A/B, SEA, SEB and Toxic shock syndrome toxin 1 ( 157 ). Preclinical data has shown that this vaccine, named IBT-V02, confers protection to both mice and rabbits against S. aureus skin infection, with protection being entirely mediated by vaccine-induced antibodies ( 142 ). Interestingly, vaccine efficacy (as measured through the development of infection-induced skin lesions) was unaffected when mice were pre-exposed intradermally to a low dose of S. aureus prior to vaccination.…”
Section: An Update Regarding Ongoing and Recently Concluded Clinical Trials For S Aureus Vaccinesmentioning
confidence: 99%